Study of the Effect of Nano Iron Oxide on Biological Feactures of Echinococcus Granulosus and Comparing it with the Aqueous Extrat of the Colocynth Plant - Nawar, Ali Mutlaq; Mahmoud, Samer Mohammed; Kazem, Nisreen Ali (Journal of Science in Medicine and Life, 2025)
Hydatidosis disease is a common disease between humans and animals and is caused by the larval stage of the tapeworm echinococcus granulosus, which is endemic in Iraq and neighboring countries. Therefore, the current study aimed to find out the effect of extracts of bitter melon and iron oxide nanoparticles on the protoscolexof E. granulosus. Isolated from the livers of infected sheep. The protoscolexisolated from the liver of sheep infected with aqueous sacs were incubated with extracts prepared in different concentrations at different intervals of 60, 30, 15, 10, 5 minutes. The average concentration of iron oxide nano, as the average concentration showed that there is a significant difference between the concentrations used to kill the vitality of the heads, and the concentration of 0.100 mg / ml achieved the highest killing rate, which amounted to 65.00%, which differed significantly from the concentrations of 0.050 and 0.025 mg / ml, which recorded a killing rate of 49.80% and 60.60% respectively. The alcoholic extract of the bitter melon plant was used from it concentrations of 1000, 500, 250 mg / ml The concentration of 1000 mg / ml differed significantly from the rest of the concentrations with a killing rate of 65.00%. Thus, the study indicates the effective role of iron oxide and alcoholic extract of the bitter melon plant in influencing the vitality of the initial heads of the beloved echinococcus.